Design Methodology for Self-organized Mobile Networks Based - Anzola, John; Bolaños Castro, Sandro Javier; Tarazona Bermúdez, Giovanny Mauricio (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2021)
The methodology proposed in this article enables a systematic design of routing algorithms based on schemes of biclustering, which allows you to respond with timely techniques, clustering heuristics proposed by a researcher, and a focused approach to routing in the choice of clusterhead nodes. This process uses heuristics aimed at improving the different costs in communication surface groups called biclusters. This methodology globally enables a variety of techniques and heuristics of clustering that have been addressed in routing algorithms, but we have not explored all possible alternatives and their different assessments. Therefore, the methodology oriented design research of routing algorithms based on biclustering schemes will allow new concepts of evolutionary routing along with the ability to adapt the topological changes that occur in self-organized data networks.
Keywords: self-organizing networks; routing methodology; biclustering algorithms; IJIMAI